Peningkatan Akurasi dan Efisiensi Operasional Sistem Reservasi dengan Metode RAD di Wilayah Yogyakarta - Pratama, Andre; Sutarman (The Indonesian Journal of Computer Science, 2025)
The event venue rental system in the Yogyakarta region, which still relies on manual processes, creates operational inefficiencies and information limitations for customers. To address this issue, this research develops an Online Event Venue Booking System using the Rapid Application Development (RAD) approach. The development is validated using the Mixed Methods approach. This system successfully implemented the main functions of place exploration and place owner management. The effective implementation of this web-based system critically addresses issues of inefficiency and recording errors through automation. Overall, the resulting system is able to optimize operational management efficiency and significantly improve the ease of the ordering process for customers.